Functional complementarity of different types of English texts - Bal Ram Adhikari (Globe, 2020)
The Faculty of Education under Tribhuvan University, Nepal, has recently shifted to a diversified approach to the selection of texts for its Bachelor of Education (B.Ed.) and Master of Education (M.Ed.) English reading courses. Apart from the conventionally prioritized native English texts, the courses incorporate texts in nativized varieties of English from international target cultures as well as texts in the emerging variety of English from students' home culture. However, in Nepal, there is a lack of research on the potential pedagogical contribution and cultural significance of texts originating from different cultures. In this respect, the present paper aims to explore university teachers' voices with regard to different types of texts and their experiences of dealing with such texts in the classroom. The qualitative data collected from six reading teachers through a semi-structured interview were analyzed thematically. Findings reveal the teachers’ awareness of functional complementarity of texts stemming from target culture, international target cultures and students' culture. As reported, different types of English texts are assumed to have complementary functions to inscribe and express local and global experiences. However, despite valuing each type of text, reading teachers tend to ascribe greater linguistic value to native English texts than nonnative texts, with the implication that the weight of native English texts continues to dominate ESL/EFL reading courses.